Riboflavin, flavin mononucleotide, and flavin adenine dinucleotide in human plasma and erythrocytes at baseline and after low-dose riboflavin supplementation - SCOTT, JOHN MARTIN (American Association for Clinical Chemistry, 2002)
Background: Vitamin B2 exists in blood as riboflavin and its cofactors, flavin mononucleotide (FMN) and FAD. The erythrocyte glutathione reductase activation coefficient (EGRAC) has traditionally been used to assess vitamin B2 status in humans. We investigated the relationships of EGRAC and plasma and erythrocyte concentrations of riboflavin, FMN, and FAD in elderly volunteers and their responses to riboflavin administration. Methods: EGRAC and plasma and erythrocyte concentrations of riboflavin, FMN, and FAD were determined in 124 healthy individuals with a mean age of 69 years. The same measurements were made in a subgroup of 46 individuals with EGRAC 1.20 who participated in a randomized double-blind 12-week intervention study and received riboflavin (1.6 mg/day; n = 23) or placebo (n = 23). Results: Median plasma concentrations were 10.5 nmol/L for riboflavin, 6.6 nmol/L for FMN, and 74 nmol/L for FAD. In erythrocytes, there were only trace amounts of riboflavin, whereas median FMN and FAD concentrations were 44 and 469 nmol/L, respectively. Erythrocyte FMN and FAD correlated with each other and with EGRAC and plasma riboflavin (P <0.05). All variables except plasma FAD responded significantly to riboflavin supplementation compared with placebo (P 0.04). The strongest increases were for riboflavin in plasma (83%) and for FMN in erythrocytes (87%). Conclusions: Concentrations of all B2 vitamers except plasma FAD are potential indicators of vitamin B2 status, and plasma riboflavin and erythrocyte FMN may be useful for the assessment of vitamin B2 status in population studies.
PUBLISHED
Keywords: Biochemistry